Faktor Dominan dari Dampak Positif Kepemilikan Sertifikat Kompetensi Kerja dalam Persepsi Tukang - Anisah; Huda Darussyafa; Irika Widiasanti (Jurnal Pensil : Pendidikan Teknik Sipil, 2020)
This study aims to determine the dominant factor of the positive impact of ownership of work competency certificates in the perception of artisan on highrise building projects in the city of South Jakarta. Based on existing data the number of workers who already have work competency certificates is still very minimal. That is caused by several factors, namely the process of implementing certification which is considered complicated to the cost which is considered expensive. But behind these constraints, work competency certificates can have a positive impact on construction workers who have them. In this study conducted by quantitative methods by analyzing the percentage of respondents' perceptions. This research was carried out on the Cithaland Tower project, Alamanda Tower, Dharmawangsa Office Tower. The total number of respondents to be studied is 44 people. In this study the dominant factor studied was measured through four indicators namely work motivation, work productivity, work ability and competitiveness. With each percentage acquisition namely for Work Motivation 26.44%, Work Productivity 24.40%, Work Ability 24.66%, and Competitiveness 24.50%. Of the four indicators there is one indicator with the highest percentage and is the most dominant factor, namely the Work Motivation indicator with a percentage of 26.44%.